Conflict resolution a pre-trial intervention - Foley, Linda A. (American journal of criminal justice, 1980)
Parties involved in interpersonal disputes often use the Criminal Justice System as a medium of retaliation. This study analyzed the effectiveness of a Citizens’ Dispute Settlement Program as an alternative to criminal prosecution. The program consists of trained volunteer hearing officers mediating between the complainant and the defendant in order to resolve the conflict without court involvement. All hearings scheduled over a six month period were studied (N-264). The hearings were categorized according to type of offense and were analyzed to determine the race and sex of the parties involved, and the effectiveness of conflict resolution efforts in each category. In general, there was no significant relationship between race and being a party in conflict. However, there was a highly significant relationship as to sex, with the majority of complainants being female, and the majority of the respondents being male. Of the scheduled hearings, 93.5% (N-247) were diverted from the court system, for an estimated savings of $80,522. The authors concluded that a Citizens’ Dispute Settlement Program, through the pretrial intervention of conflict resolution efforts, provides an effective means of alleviating the congestion in our courts.